Elisha Hunt Allen papers - Allen, Elisha Hunt, 1804-1883.
Correspondence including family correspondence and official letters (1877-1882) sent from the Hawaiian legation, speeches, notes, statistical tables, passports, invitations, awards, diplomas, miscellaneous printed matter, and photographs concerning Hawaiian economic and political conditions, sugar plantations and trade, Chinese labor, Hawaiian Supreme Court (of which Allen was chief justice), and the U.S.-Hawaiian Reciprocity Treaty of 1876. Correspondents include Allen's second wife, Mary Hobbs Allen; Charles Reed Bishop; W.L. Green; Charles Coffin Harris; Kalakaua, David, King of Hawaii; Henry W. Severance; and Andrew Welch.
Diplomat, jurist, lawyer, and U.S. representative from Maine.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Allen, Mary Hobbs -- Correspondence; Bishop, Charles Reed, -- 1822-1915 -- Correspondence; Green, W. L. -- Correspondence; Harris, Charles Coffin, -- 1822-1881 -- Correspondence; Kalakaua, David, -- King of Hawaii, -- 1836-1891.; Severance, Henry W. -- Correspondence; Welch, Andrew, -- active 1876-82 -- Correspondence; Hawaii. -- Supreme Court; Chinese -- Hawaii; Courts -- Hawaii; Plantations -- Hawaii; Reciprocity (Commerce); Sugar trade -- Hawaii; Working class -- Hawaii; Hawaii -- Economic conditions; Hawaii -- Foreign relations -- United States; Hawaii -- Politics and government -- To 1893.; Maine -- Politics and government; United States -- Foreign relations -- Treaties; United States -- Foreign relations -- Hawaii; Diplomats; Jurists; Lawyers; Representatives, U.S. Congress -- Maine